Impact of surface chemistry - Somorjai, Gabor A.; Li, Yimin; Yates, John T. (Proceedings of the National Academy of Sciences - PNAS, 2011)
The applications of molecular surface chemistry in heterogeneous catalyst technology, semiconductor-based technology, medical technology, anticorrosion and lubricant technology, and nanotechnology are highlighted in this perspective. The evolution of surface chemistry at the molecular level is reviewed, and the key roles of surface instrumentation developments for in situ studies of the gas—solid, liquid—solid, and solid—solid interfaces under reaction conditions are emphasized.